2017
DOI: 10.1177/0891241617744861
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Impression Management in Ethnographic Research

Abstract: In this article, we contend that turning a sharp dramaturgical lens on the dynamics of fieldwork clarifies a number of longstanding ethical challenges in ethnography—challenges that have shifted and deepened in the new technological landscape in which ethnographers work. We encourage fieldworkers to adopt an intentional approach to what we call methodological impression management to navigate the research process more strategically. Drawing on our experiences conducting fieldwork in settings where some of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Opportunities to gain access and insight depend on the quality of the social relationships between the ethnographer and the people in the field. In the literature, this relationship is predominantly conceptualized with recourse to sociopsychological theories of interaction and/or identity (Gengler and Ezzell 2017; Harrington 2003; Lipson 1991). Metaphorically speaking, this theorizing of fieldwork caricatures a dramaturgical approach of “we can all play ethnographer.” We simply have to be knowledgeable about the huge repertoire of methodology that provides us with countless “stage directions” for appropriate “role play” to help us gain access to fields and maximize our informational yield (e.g., Snow, Benford, and Anderson 1986).…”
Section: Extra-methodological Researcher Dispositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opportunities to gain access and insight depend on the quality of the social relationships between the ethnographer and the people in the field. In the literature, this relationship is predominantly conceptualized with recourse to sociopsychological theories of interaction and/or identity (Gengler and Ezzell 2017; Harrington 2003; Lipson 1991). Metaphorically speaking, this theorizing of fieldwork caricatures a dramaturgical approach of “we can all play ethnographer.” We simply have to be knowledgeable about the huge repertoire of methodology that provides us with countless “stage directions” for appropriate “role play” to help us gain access to fields and maximize our informational yield (e.g., Snow, Benford, and Anderson 1986).…”
Section: Extra-methodological Researcher Dispositionsmentioning
confidence: 99%
“…As recommendable as the staging of the buddy–researcher proved to be in my case (cf., methodological impression management; Gengler and Ezzell 2017), I propose that performing this role is only feasible if the ethnographer is already equipped with field-adequate sociocultural competencies. On the one hand, the researchers influence how they are perceived by others via means of intentional “expressions given” (Goffman 1959, 4–16), which are to convey a certain favorable image.…”
Section: Incomplete or Vague Guidelines: Extra-methodologically Informentioning
confidence: 99%
“…Third, symbolic meanings are often contested, and ethnographers may observe participants expressing resistance to the rituals. Simultaneously, participants watch researchers to gauge their reactions to rituals, requiring ethnographers to be especially careful about how they construct and maintain their presentation of ethnographic self (Gengler and Ezzell 2018). In a study of ritualized practices in health care, Waring and Bishop (2010) found that workplace rituals were “an end in themselves” and not treated as sacred by participants in the setting.…”
Section: Literature and Theorymentioning
confidence: 99%
“…It is only after I concluded my employment and distanced myself from the organization that I was able to gain some perspective and consider my own “ethical reflexivity” (Reed-Danahay 2002). Immersed in H-West, I also struggled with what Gengler and Ezzell (2018) call “methodological impression management” in terms of balancing ethical obligations with the “analytic rigor” of my findings (809).…”
Section: Reflections and Concluding Thoughtsmentioning
confidence: 99%